The Effect of Antihelminthic Treatment on Subjects with Asthma from an Endemic Area of Schistosomiasis: A Randomized, Double-Blinded, and Placebo-Controlled Trial - Maria Cecilia F. Almeida; Givaneide S. Lima; Luciana S. Cardoso; Robson P. de Souza; Régis A. Campos; Alvaro A. Cruz; Joanemile P. Figueiredo; Ricardo R. Oliveira; Edgar M. Carvalho; Maria Ilma Araujo (Journal of Parasitology Research)
This is a prospective, double-blinded, and placebo-controlled trial evaluating the influence of antihelminthic treatments on asthma severity in individuals living in an endemic area of schistosomiasis. Patients from group 1 received placebo of Albendazole or of Praziquantel and from group 2 received Albendazole and Praziquantel. Asthma severity was assessed by clinical scores and by pulmonary function test. There was no significant difference in the asthma scores from D0 to D1–D7 after Albendazole or Praziquantel and from D0 to D30–90 after Albendazole or Praziquantel in both, group 1 and 2. It was observed, however, a clinical worsening of the overall studied population after 6 months and 12 months of antihelminthic treatments. Additionally, we observed increased frequency of forced expiratory volume in 1 second (FEV1) <80% on 12 and 18 months after treatment. The worsening of asthma severity after repeated antihelminthic treatments is consistent with the hypothesis of the protective role conferred by helminths in atopic diseases.